SENYAWA BIOAKTIF MIKROALGA DAN PROSPEKNYA DI MASA DEPAN - Indyaswan Tegar Suryaningtyas (OSEANA, 2019)
BIOACTIVE COMPOUND FROM MICROALGAE AND ITS FUTURE PROSPECT. Microalgae biomass is potential to be used in various fields, one of which is as a producer of bioactive compounds. Bioactive compounds from microalgae can be used extensively in the pharmaceutical industry, cosmetic’s raw materials, food flavouring substances, and functional food ingredients. In terms of health, the bioactive compounds have the potential as antioxidants, antiviral, antibacterial, anti-fungal, anti-inflammatory, anti-tumor, and prevent the effects of malaria, but the potential for microalgae’s bioactive compound has not been explored well if compared to the production of terrestrial plants. Some examples of the bioactive compounds that have been used are carotenoid groups such as lutein, β-carotene, astaxanthin and fucoxanthin; fatty acid groups such as EPA and DHA; and also some toxin compounds such as domoic acid. To obtain the optimum yield of bioactive compounds, it requires the right method in biomass production, compound extraction, compounds isolation and compounds identification. While testing the activities, it is necessary to do some assays such as antioxidan, antibiotic, antiviral and anticancer assay. The development of the technology can improve the potential use of microalgae to synthesis its bioactive compounds.